2013
DOI: 10.1021/bi400021b
|View full text |Cite
|
Sign up to set email alerts
|

Single-Domain Metallothioneins: Evidence of the Onset of Clustered Metal Binding Domains in Zn-rhMT 1a

Abstract: Mammalian metallothioneins bind up to seven Zn(2+) ions in two distinct domains: an N-terminal β-domain that binds three Zn(2+) ions and a C-terminal α-domain that binds four Zn(2+) ions. Domain specificity has been invoked in the metalation mechanism with cluster formation and bridging of the 20 Cys residues taking place prior to saturation with seven Zn(2+) ions. We report a novel experiment that examines Zn(2+) metalation by exploiting the expected decrease in K(F) at the onset of clustering using electrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 54 publications
3
38
1
Order By: Relevance
“…This process has been recently discussed for Zn-MT. [43] The structural determinants for this process are unknown. However, elucidation of The metal-induced folding of apo-a-MT is driven by the stepwise formation of the metal-thiolate cluster within the core of the domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process has been recently discussed for Zn-MT. [43] The structural determinants for this process are unknown. However, elucidation of The metal-induced folding of apo-a-MT is driven by the stepwise formation of the metal-thiolate cluster within the core of the domain.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that in the globular conformation, the cysteine residues are prearranged to the correct orientation for cluster formation and therefore, this final rearrangement step is fast. The denatured protein may be able to bind the first two metals more quickly in a bead-like structure previously described, [43] but once bridging cysteines are required for the cluster structure, the necessary structural rearrangement is much slower. Although one might expect the open, string-like conformation to metalate more rapidly due to the increased accessibility of cysteine residues compared to the globular state, the results of the metalation experiment with Cd II show unambiguously that the opposite is true.…”
mentioning
confidence: 82%
“…233 Finally, titrations of human apo-MT-1a with various metal ions including Zn 2+ using a stopped-flow approach showed that this MT also binds these metal ions non-cooperatively, as yet again the observed metallo-species did not indicate a preference for complete clusters. 235,236 Since MTs can be populated by cadmium in vivo, 177,178 it is of interest to study the replacement of Zn 2+ by Cd 2+ . Spectrophotometric analysis of the kinetics of Cd 2+ /Zn 2+ exchange in rabbit MT-2 as well as the isolated a domain revealed that metal exchange occurs via an associative mechanism, with the incoming Cd 2+ initially binding to the fully metallated MT, followed by exchange with a bound Zn 2+ .…”
Section: View Article Onlinementioning
confidence: 99%
“…26,28,47,49 In the formation of metal-saturated final products, the MTs pass through partially-metalated 56 Assuming that the metalation reactions follow a purely domain-specific mechanism, it is likely that the separated domains would enhance this feature since interdomain interactions that would result in property differences between the separated domains and intact protein are reduced. 53 We will return to discuss evidence for interdomain interactions below.…”
Section: Discussionmentioning
confidence: 99%